Comparing laparoscopic surgery with open surgery for long-term outcomes in patients with stage I to III colon cancer. (June 2018) - Ringressi, Maria Novella; Boni, Luca; Freschi, Giancarlo; Scaringi, Stefano; Indennitate, Gianpiero; Bartolini, Ilenia; Bechi, Paolo; Taddei, Antonio
Abstract: Background: Although the short-term advantages of laparoscopy for colon cancer (CC) over open surgery have been clearly demonstrated, there is little evidence available concerning the long-term outcomes. This study aimed to compare the long-term results of laparoscopic surgery versus open surgery in a cohort of CC patients from a single center. Methods: A series of 443 patients consecutively operated on for stage I to III CC between January 2006 and December 2013 were followed up. Patients were divided into two groups according to the surgical technique and were compared for disease-free survival (DFS) and overall survival (OS) before and after 1:1 propensity score matching. Results: Due to exclusions and drop-outs, the statistical analysis of the study is based on 398 patients. Open surgery was performed in 133 patients, and laparoscopic surgery was performed in 265. After propensity score matching, two comparable groups of 89 patients each were obtained. The 5-year DFS was 64.3% and 78.2% for patients in the open and laparoscopic resection groups, respectively [hazard ratio (HR) 0.63, 95% confidence interval (CI) 0.33–1.19; P = 0.148]. A 5-year OS of 72.1% and 86.8% was observed in the open and laparoscopic resection groups, respectively (HR 0.43, 95%CI 0.20–0.94; P = 0.026). The multivariate survival analysis demonstrated better results of laparoscopy compared with open surgery for both DFS (HR 0.43, 95%CI 0.23–0.78; P = 0.004) and OS (HR 0.28, 95%CI 0.14–0.59; P < 0.001). Conclusions: Despite the limitations of a retrospective analysis, our study confirms better results for laparoscopic surgery in terms of DFS and OS compared with open surgery in CC treatment. Highlights: Long term outcomes of open and laparoscopic surgery in a cohort of colon cancer patients were investigated and compared. Compared to open surgery, laparoscopic approach was associated with better results in terms of both DFS and OS. The probability of having 12 or more lymph nodes retrieved/analyzed did not differ between the two surgical techniques. Minimally invasive surgery should be considered the standard for the treatment of patients with non-advanced colon cancer.